(untitled) (Práxis Educativa, 2024)
The objective was to analyze the management of 156 managers of rural Peruvian institutions of intercultural bilingual education for three years (A01,02.03) in confinement due to Covid-19, covering pluralistic and democratic linguistic policies (D1), development of students’ potentialities (D2) and multilingual and multicultural virtual spaces (D3). Exploratory, confirmatory factor analysis and ANOVA were evaluated. The results demonstrate: validity of the instrument, consistency of its correlations and analysis of variance. In D1 for A01 59.4±10.5%, for A02 65.4±10.9%, and for A03 70.2±11.6% evidencing an inadequate implementation of pluralistic and democratic linguistic policies. In D2 for A01 75.1±4.6%, for A02 58.5±6.5% and for A03 75.0±7.9%, demonstrating that multilingual educational models do not integrate or allow the development of students’ potential. In D3, for A01 75.1±4.6%, for A02 73.5±2.5% and for A03 74.2±8.5%, pointing out that virtual spaces limit the development and integration of bilingual students. Keywords: Management. Bilingual Intercultural Education. Covid-19.